Analysis of Emotional Stress of Teachers in Japanese Teaching Process Based on EEG Signal Analysis - Jie Dong (Occupational Therapy International)
The construction direction of Japanese teaching evaluation system based on hybrid teaching mode is to give full feedback to teaching process, diversify evaluation subjects and evaluation methods, and obtain comprehensive and objective evaluation results. Compared with most similar studies, more EEG data of teachers’ emotional stress relief and healthy people in Japanese teaching process were collected, and a large number of features were extracted. An experiment of teachers’ emotional stress relief recognition in Japanese teaching process based on EEG signal was designed. The feature selection algorithm was used to screen the EEG feature combinations of teachers’ emotional stress relief and healthy subjects, and the classification experiment was carried out to verify the difference. Finally, this paper uses the feature selection algorithm of tree model and the random forest model classifier to establish the recognition model of teachers’ emotional stress discharge in Japanese teaching process based on EEG signals and achieves the effect of more accurate recognition of teachers’ emotional stress discharge in Japanese teaching process. First, the connotation, value, and influencing factors of teachers’ emotion management ability are logically integrated and systematically expounded. Second, based on emotional psychology, emotional intelligence theory, psychotherapy theory, and management theory, teachers’ emotional management ability is constructed according to the three-dimensional structure theory of intelligence and information processing theory. It is constructed from three dimensions: object dimension (teachers themselves, students, and students), content dimension (positive and negative emotions), and operational dimension (emotional perception, emotional understanding, emotional expression, and emotional regulation).